A bibliometric and visualized research on global trends of immune checkpoint inhibitors related complications in melanoma, 2011–2021 - Zhang, Hongyi; Shi, Yanlong; Ying, Jianghui; Chen, Yi; Guo, Rong; Zhao, Xin; Jia, Lingling; Xiong, Jiachao; Jiang, Fei (Frontiers in Endocrinology, 2023)
Background: Melanoma is a malignant tumor originating from the canceration of melanocytes with high rate of invasiveness and lethality. Immune escape has been regarded as an important mechanism for tumor development, while the treatment of immune checkpoint inhibitors (ICIs) is beneficial to restore and enhance the body's anti-tumor immune response to kill tumor cells. To date, ICIs therapy has achieved remarkable efficacy in the treatment of melanoma patients. Despite the significant clinical benefits of ICIs, multiple complications such as rashes, thyroiditis, and colitis occur in melanoma patients. In this study, we aim to explore the development process and trends in the field of ICIs related complications in melanoma, analyze current hot topics and predict future research directions. Methods: We screened most relevant literatures on ICIs related complications in melanoma in the Web of Science Core Collection (WoSCC) from 2011 to 2021, and analyzed research trends in this field by VOSviewer, CiteSpace and R language packages. Results: A total of 1,087 articles were screened. The USA ranks first in the number of publications (publications = 454, citations = 60,483), followed by Germany (publications = 155, citations = 27,743) and Italy (publications = 139, citations = 27,837). Memorial sloan kettering cancer center is the institution with the most publications, but the angeles clinic and research institute achievements a have the highest average citation rate. Lancet oncology (IF, 2021 = 54.43) is the most prominent of all journals in terms of average citation rate. References and keyword cluster analysis showed that anti-tumor efficacy, adjuvant treatment, clinical response, clinical outcome, etc. are the hotspots and trends of research in recent years. Conclusions: This study provides a comprehensive summary and analysis of global research trends on ICIs related complications in melanoma. In the past 10 years, the number of publications about ICIs related complications in melanoma has increased significantly. The safety and benefits of retreatment after the recovery of ICIs-related complications are unknown, thus the establishment of related prediction models and the immunotherapy of melanoma with ICIs in combination with other adjuvant therapies are the future research hotspots.